PENGARUH KARAKTERISTIK PEKERJAAN DAN PERSON ORGANIZATION FIT TERHADAP KINERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Pada PT.Wirasta Guna Mandiri Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The effect of job characteristics and po fit on employee performance with OCB mediation at PT.Wirasta Guna Mandiri Semarang. Good performance requires employees are not just doing the basic job description but also working that is outside the main job. It is called extra role performance that is not instantly recognizable in a formal work system that supports effective functioning of the organization. OCB is a kind of employees contribution that exceeds the demands of their role in the workplace and they get reward by the acquisition of task performance. This behavior illustrates the added value of employees and it is one of prosocial. The leader’s job won’t be difficult if there are employees with high OCB. This study aims to determine whether the effect of Job Characteristics and Person Organizatinal Fit to employee performance with the mediation of OCB at PT.Wirasta Guna mandiri semarang. This research provides empirical evidence as follows: (1) The characteristics of the work and Po Fit have positive effect related to OCB (2) OCB, job characteristics and Po fit have positive effect related to employee performance (3) OCB mediate job characteristics and employee performance (4) OCB does not mediate Po Fit and employee performance. Keywords: Job Characteristic, Person Organizatinal Fit, Organizational Citizenship Behavior